Some Clinical Trials Get No Respect - Richard Conti, C. (Clin Cardiol, 2009)
There is something to be learned from every randomized clinical trial. However, because of physician bias and/or misinterpretation by the cardiovascular community and by the lay press, some trials seem to generate a lot of heat before they generate light. This is particularly true for trials comparing medical therapy to revascularization, (eg, PCI/stent or coronary artery bypass surgery). Copyright © 2009 Wiley Periodicals, Inc.